Station for Measuring Ecosystem–Atmosphere Relations (SMEAR II) - Hari, P.; Kulmala, M. (Boreal Environment Research Publishing Board, 2024)
Here we present the ongoing SMEAR (Station for Measuring Forest Ecosystem–Atmosphere Relations) research program and also related future views. The main idea of SMEAR-type infrastructures is continuous, comprehensive measurements of fluxes, storages and concentrations in the land ecosystem–atmosphere continuum. The major coupling mechanisms between atmosphere and land surface are the fluxes of energy, momentum, water, carbon dioxide, atmospheric trace gases and atmospheric aerosols. Understanding of couplings and feedbacks is the basis for the prediction of changes in the system formed by atmosphere, vegetation and soil. A better quantification of the agents that cause climate change, as well as the emissions and removals of species, will provide more accurate projections of future atmospheric composition and hence climate.